Experience and side effects of COVID-19 vaccine uptake among university students: a cross-sectional survey study - Islam, Md. Akhtarul; Nahar, Mst. Tanmin; Rahman, Abdur; Monjur Al Hossain, A. S. M.; Jui, Umme Johra; Tabassum, Tarana; Barna, Sutapa Dey; Tahmida, Shafia; Mishu, Afrina Akter; Parvin, Shahanaj; Naime, Jannatul; Attar, Razaz Waheeb; et al. (Frontiers in Public Health, 2024)
Introduction: Many people expressed concern over coronavirus vaccinations’ reliability and side effects. This research aimed to assess university students’ perceptions and experiences regarding the side effects of the COVID-19 vaccines in Bangladesh. Method: We conducted an online cross-sectional survey to collect responses from university students vaccinated with any vaccines administered in Bangladesh between November 2021 to April 2022. Bangladeshi university students over the age of 18 and having an internet connection wasincluded in the study. A binary logistic regression analysis along with Pearson’s Chi-square test were used to identify COVID-19 vaccine-related side effects predictors after receiving the first dose. Results: A total of 1176 participants responded voluntarily to the online study, and most were vaccinated. More than half of the participants received the Sinopharm vaccine (56.5%), while others received Covishield (8.9%), Moderna (7.3%), and Pfizer (5.8%) vaccine. Around 32% of the participants reported side effects after receiving the first dose of the vaccine, including pain and edema (78.4%), body temperature (20.3%), and headache (14.5%), while a few experienced allergy, anxiety, and uneasy feelings. About 17% of the participants reported experiencing side effects after the second dose of the vaccine, including pain and edema (7.5%), body temperature (8.8%), and headache (7.3%). Most side effects were significantly associated with the Moderna vaccine (p < .001). Female students and those previously infected with COVID-19 were significantly associated with the side effects after taking the first dose of the vaccine. Conclusion: We found that side effects are mild and did not pose a significant challenge to Bangladesh’s effort in managing and reducing the risk associated with the COVID-19 pandemic.